The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1001/archotol.126.5.585
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tympanostomy Tubes on Child Quality of Life

Abstract: Tympanostomy tubes produce large short-term improvements in QOL for most children. The best outcomes occur when postoperative otorrhea is absent or minimal, and when parents are satisfied with their initial decision to have surgery. Further research is needed to document the long-term impact of tubes on child QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
164
2
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(190 citation statements)
references
References 29 publications
15
164
2
9
Order By: Relevance
“…The manual search and expert discussion yielded one extra article [28]. After applying the criteria for inclusion and exclusion, only 13 articles remained for inclusion [29,30,[35][36][37][38][39][40][41][42][43][44]. In addition, we included results regarding reliability and validity of the TAIQOL from our own work published in a thesis [45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manual search and expert discussion yielded one extra article [28]. After applying the criteria for inclusion and exclusion, only 13 articles remained for inclusion [29,30,[35][36][37][38][39][40][41][42][43][44]. In addition, we included results regarding reliability and validity of the TAIQOL from our own work published in a thesis [45].…”
Section: Resultsmentioning
confidence: 99%
“…The setting of the studies varied, eight studies were part of a multi-centre trial [28,35,37,38,41,[43][44][45]. Most study-populations consisted of children with chronic or recurrent otitis media ( Table 2).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…In particular, several studies have been published investigating the effect of tympanostomy tube placement on their FHS, with some showing a positive effect 5,45,48,49 and others not. 50 Trials on tympanostomy tube placement, however, are hampered by the inability to blind caregivers and children for treatment, which means that treatment effects may be at least in part biased by their expectations.…”
Section: Discussionmentioning
confidence: 99%
“…207 Tympanostomy tube insertion has been shown to improve diseasespecific quality-of-life measures in children with OM. 208 One multicenter, nonrandomized observational study showed large improvements in a disease-specific quality-of-life instrument that measured psychosocial domains of physical suffering, hearing loss, speech impairment, emotional distress, activity limitations, and caregiver concerns that are associated with ear infections. 209 These benefits of tympanostomy tubes have been demonstrated in mixed populations of children that include children with OME as well as recurrent AOM.…”
Section: Surgery For Recurrent Aommentioning
confidence: 99%